Minorities, Ethnicity and Culture in a Global World Seen from a Dane's Point of View - Nagbøl, Søren (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
Using a sociological figuration model the paper addresses the theme of the “Establishment and the Outsiders - A sociological enquiry into community problems”. In this context, the paper examines the risks and problems related to the changing of subjectivity in late modernity on different levels, for instance, by dealing with processes connected to encounters between so-called “natives” in a country and immigrants - in other words, between the established and outsiders.